A transnational and holistic breeding approach is needed for sustainable wheat production in the Baltic Sea region. Issue 4 (25th April 2018) - Chawade, Aakash; Armoniené, Rita; Berg, Gunilla; Brazauskas, Gintaras; Frostgård, Gunilla; Geleta, Mulatu; Gorash, Andrii; Henriksson, Tina; Himanen, Kristiina; Ingver, Anne; Johansson, Eva; Jørgensen, Lise Nistrup; et al.
Abstract : The Baltic Sea is one of the largest brackish water bodies in the world. Eutrophication is a major concern in the Baltic Sea due to the leakage of nutrients to the sea with agriculture being the primary source. Wheat ( Triticum aestivum L.) is the most widely grown crop in the countries surrounding the Baltic Sea and thus promoting sustainable agriculture practices for wheat cultivation will have a major impact on reducing pollution in the Baltic Sea. This approach requires identifying and addressing key challenges for sustainable wheat production in the region. Implementing new technologies for climate‐friendly breeding and digital farming across all surrounding countries should promote sustainable intensification of agriculture in the region. In this review, we highlight major challenges for wheat cultivation in the Baltic Sea region and discuss various solutions integrating transnational collaboration for pre‐breeding and technology sharing to accelerate development of low input wheat cultivars with improved host plant resistance to pathogen and enhanced adaptability to the changing climate.